IMPACT OF THE PANDEMIC COVID-19 ON THE ACTIVE LIVING BEHAVIOR OF JUNIOR HIGH SCHOOL STUDENTS IN WEST JAVA - Tarigan, Beltasar; Murtiansyah, Wisnu; Hidayat, Teten (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the impact of the pandemic Covid -19 on the active life behavior of junior high school students in West Java. The populace used became junior high college students in West Java, and a random sample of 1854 college students was represented from each district. The sampling method used an easy random technique (random sampling). The studies approach used a descriptive quantitative approach. The tool became a physical activity questionnaire for kids (PAQ-C). Data evaluation using Microsoft Excel and SPSS 24, the outcomes are as follows: The active life conduct of junior excessive school students before the pandemic Covid-19 changed into distributed within the mildest class as many as 1099 humans (59%) and at some point of the Covid-19 pandemic the highest distribution turned into within the low category as many as 1,075 humans (58%). Physical sports completed using junior high school college students in West Java before the pandemic Covid-19 were jogging, conventional sports, soccer, volleyball, badminton, basketball, futsal, self-protection, energy education, gymnastics, and even physical activities in the course of the pandemic Covid-19 have been sunbathing, walking, jogging, cycling. Maximum bodily interests are assisting the aged. For the duration of the Covid-19 pandemic, the impact on college students' physical hobbies reduced from the medium category to the low class.